Study on mastering data for tourism by EU destinations. - Galasso, Giovanna; Montino, Carlo; Sidoti, Alessio; Mureddu, Francesco; Peláez-Verdet, Antonio; Cerezo-Medina, Alfonso; Collado, Antonio (Publications Office of the European Union, 2022)
In the European Union, tourism represents one of the main sectors for job and business creation, source of income, and territorial development. Moreover, tourism has social, cultural, and environmental implications, as it can greatly contribute to social cohesion, poverty eradication, and conservation and promotion of cultural and naturalistic heritage. At the same time, tourism can also generate adverse impacts on destinations and residents if its activities are not managed sustainably. Disparities in regional development, pressure on environmental ecosystems, deterioration of resident population quality of life are just a few of the most common drawbacks in connection with poorly managed tourism activities, which are sometimes worsened by the intrinsic characteristics of the sector, such as seasonality. For these reasons, it is of the utmost importance to ensure that tourism policies are geared toward an ever-stronger promotion of growth, while at the same time embracing the essential principles of sustainable development. In this context, the diffusion of technologies applied to tourism represent a pivotal element to support effective and efficient tourism management, as well as to unlock the benefits offered by the sector to communities and destinations. The present report – delivered in the context of the “Smart Tourism Destinations” project funded by the European Commission – aims at contributing to the knowledge base for European destinations wanting to become smarter in their development and management of tourism. In particular, it focuses on how European destinations are nowadays making use of data for tourism, outlining features and enabling conditions, challenges, good practices, trends, cases of cooperation, and proposing a preliminary set of recommendations for future action.
Keywords: Turismo - Unión Europea; Europe; Coronavirus disease; Cultural heritage; Data processing; Decision making; Economic growth; Impact study; Regional development; Regional disparity; Sustainable mobility; Tourism; Town planning